Pengaruh Kombinasi Tepung Sagu dan Tepung Udang Rebon terhadap Karakteristik Kimia dan Organoleptik Makaroni: Characteristics of makaroni based on sago flour, combined with rebon shrimp flour (Acetes erythraeus) - Suparmi Suparmi; Sumarto Sumarto; Nur Ira Sari; Taufik Hidayat (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2021)
This study was aimed to determine the characteristics of fortified sago flour macaroni with rebon shrimp flour. The method used is an experimental method using a completely randomized design, with three combinations of sago flour and rebon shrimp flour, namely MS0 (control without rebon shrimp flour), MS1. (combination 2: 1) and MS2 (combination 1: 1) is repeated 3 times. The parameters tested were proximate quality (water content, ash content, protein content, fat content, and carbohydrate content), water absorption capacity and organoleptic quality (appearance, texture, aroma, taste). The results showed that the making of sago flour macaroni with the addition of rebon shrimp flour had a significant effect on the proximate value, water absorption and organoleptic value. The best treatment is MS1 (2:1 combination) which has visual characteristics with bright yellow color, fishy aroma of shrimp, solid texture not hard, and savory taste. The value of protein (19.67%) water (6.98%), fat (4.13%), ash (2.57%), and carbohydrates (by difference) was 65.65%. Over all, the addition of rebon shrimp flour as much as 50 percent can increase protein, ash, and fat which have the potential for functional food.